First report of Aspergillus sydowii and Aspergillus brasiliensis as phosphorus solubilizers in maize - Baron, Noemi Carla [UNESP]; Costa, Nágila Torrini Alves [UNESP]; Mochi, Dinalva Alves [UNESP]; Rigobelo, Everlon Cid [UNESP] (Springer Nature, 2018)
Maize is one of the most important crops worldwide. It provides food for humans and animals and is used in biotechnological and industrial processes to produce a wide variety of products. The phosphorus (P) requirement for its development and production is high, but the absorption efficiency of this nutrient is insufficient to meet its requirements. The use of P-solubilizing fungi can increase this efficiency, thus reducing the amount of fertilizers applied to the crops. Therefore, this study aimed to verify the potential use of A. sydowii and A. brasiliensis and their effect in the field as bioinoculants when associated with three P fertilization doses. The experiment was carried out in a maize field, and treatments were presence and absence of fungi associated with P mineral fertilization doses. The parameters evaluated were shoot dry matter, P content in the plant, and P content in the soil. A. sydowii caused the highest P content in the plant and soil at fertilization doses of 75% and 100%, contradicting the expected results from in vitro assays that indicated that A. brasiliensis would provide better rates of P uptake. There was no difference in the other fertilization doses or for dry matter when comparing all treatments. This result strongly suggests that the use of A. sydowii can improve the efficiency of P absorption with fertilization application. In addition, the molecular analysis of the two fungi performed in this study contributes novel information on the use of both species during the agricultural process.
Keywords: Aspergillus brasiliensis; Aspergillus sydowii; Fertilization reduction; Maize; Phosphate solubilization; Phosphorous uptake